Effects of Bifidobacterium bifidum and Enterococcus faecium incorporation on qualitative attributes of Iranian ultra-filtrated Feta cheese - Mortazavian, A. M. (2024)
The present work determined the effect of Bifidobacterium bifidum and Enterococcus faecium incorporation on the qualitative attributes of ultra-filtrated (UF) Feta cheese. The alterations in pH, titratable acidity, proteolysis, and lipolysis were evaluated during 60 days of refrigerated storage. Viable count, optical analysis, and sensory evaluation were also performed on the freshly made cheeses throughout the storage period. Results showed that incorporating B. bifidum and E. faecium, either individually or in combination, significantly decreased the pH values as compared to control. Cheeses incorporated with E. faecium had significantly higher titratable acidity, proteolysis, and lipolysis than the other treatments. Probiotics counts were higher than 10⁶ CFU/g at the end of the storage period. Co-inoculation of both probiotics did not enhance the viability of either. Moreover, the colour of UF Feta cheeses was not influenced by the incorporation of B. bifidum and E. faecium. The other sensory features remained unchanged on the first day of refrigerated storage. Overall, B. bifidum and E. faecium could be promising species for industrial production of probiotic UF Feta cheeses.